1983
DOI: 10.1111/1523-1747.ep12535038
|View full text |Cite
|
Sign up to set email alerts
|

Increased Concentrations of Arachidonic Acid, Prostaglandins E2, D2, and 6-oxo-F1α, and Histamine in Human Skin Following UVA Irradiation

Abstract: The buttock skin of clinically normal human subjects was subjected to approximately 2.5 minimal erythema doses of ultraviolet A irradiation. Deep red erythema developed during irradiation, faded slightly within the next few hours, increased to maximum intensity between 9-15 h, and decreased gradually thereafter although still persisting strongly at 48 h. Suction blister exudates were obtained at 0, 5, 9, 15, 24, and 48 h after irradiation as well as suction blister exudates from a contralateral control site an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…Despite di erences in animal species and in the amounts and methods used for UVR, several authors have reported long lasting changes in neuropeptides (Benrath et al, 1995;Eschenfelder et al, 1995;Gillardon et al, 1992;Greaves & Sùndergaard, 1970;Polga r et al, 1998), histamine and prostaglandins (Greaves & Sùndergaard, 1970;Hawk et al, 1983) and other mediators known to contribute to the in¯ammatory reaction (for review, see Hruza & Pentland, 1993). Increased levels of proin¯ammatory and antiin¯am-matory cytokines in the skin or in the plasma have also been observed following UVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite di erences in animal species and in the amounts and methods used for UVR, several authors have reported long lasting changes in neuropeptides (Benrath et al, 1995;Eschenfelder et al, 1995;Gillardon et al, 1992;Greaves & Sùndergaard, 1970;Polga r et al, 1998), histamine and prostaglandins (Greaves & Sùndergaard, 1970;Hawk et al, 1983) and other mediators known to contribute to the in¯ammatory reaction (for review, see Hruza & Pentland, 1993). Increased levels of proin¯ammatory and antiin¯am-matory cytokines in the skin or in the plasma have also been observed following UVR.…”
Section: Discussionmentioning
confidence: 99%
“…Skin in¯ammation due to acute exposure to UVR has been shown to be characterized by the release of neuropeptides, histamine, prostaglandins, serotonin and oxygen radicals (Benrath et al, 1995;Eschenfelder et al, 1995;Greaves & Sùndergaard, 1970;Hawk et al, 1983;Hruza & Pentland, 1993) and the upregulation of proin¯ammatory cytokines, such as interleukin (IL)-1 (Araneo et al, 1989;Gahring et al, 1984;Kupper et al 1987) and IL-6 and tumour necrosis factor alpha (TNF-a) (KoÈ ck et al, 1990;Oxholm et al, 1988). Prolonged or repetitive exposure to UVB, however, has been reported to lead to generalized immunosuppression (Streilein et al, 1994) through the production/secretion of antiin¯ammatory cytokines such as IL-4, and IL-10 (Araneo et al, 1989;Rivas & Ullrich, 1992;Shreedhar et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in PG E 2 , D 2 and prostacyclin after UVA irradiation is also dose-dependent and reaches maximum levels 5-9 h after exposure. After 15 h, these substances begin to decrease and finally return to basal levels 24 h later (8). PG E 2 seems to be involved in the epidermal growth resulting from the exposure and increased vascular permeability (85) through the increase in leukotriene C4 levels.…”
Section: Biochemical Mediators In the Pathogenesis Of Erythemamentioning
confidence: 99%
“…Other signs and symptoms include skin sensitivity to touch, as well as edema, discomfort and pain. Delayed pigmentation or tanning begins after the second or third day and, finally, after a period of 6 to 10 days peeling can occur (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose ester films containing 3% dithranol were prepared as previously described (Schroot et al, 1984 , (1983b) for the dithranol experiment. PGE2 and 12-HETE were analysed by gas chromatography-mass spectrometry as previously described (Hawk et al, 1983;Barr et al, 1984b). Fractions co-chromatographing with LTB4 were analysed for chemokinetic activity with the agarose microdroplet chemokinesis assay using human neutrophils (Camp et al, 1983b were low (< 100 pg ml[') and close to the limits of the assay; small increases were not significant.…”
Section: Introductionmentioning
confidence: 99%